Aspects of death and the afterlife in Greek literature - Gazis, George Alexander; Hooper, Anthony (Liverpool University Press, 2021)
The concept of the afterlife has always been prominent in both Greek literature and modern scholarship alike. The fate of man after his/her allotted time has come to an end has a central position in poetry, philosophy and religion, often leading to questions and answers as to how one can best live one's life, and how can one deal with the burden of mortality that is inherent in every human being. The Greeks devoted a considerable amount of their literary production in an attempt to answer these questions through a variety of different media, whereas similar concerns appear to have been at the core of the ancient world in general. This volume represents the first to examine the influences, intersections, and developments of understandings of death and the afterlife between poetic, religious, and philosophical traditions in ancient Greece in one resource. Greek thinking on death and the afterlife was neither uniform, simple, nor static, and by offering an examination of these matters in a properly interdisciplinary context this collection of papers aims to demonstrate the full richness, complexity, and flexibility of these ideas in the ancient Greek world, and illuminate how freely writers from various genres drew inspiration from each other's thinking concerning eschatological matters. Contributors: Alberto Benarbé; Rick Benitez; Nicolo Benzi; Chiara Blanco; Radcliffe Edmonds; George Alexander Gazis; Anthony Hooper; Vaios Liapis; Alex Long; Ioannis Ziogas.